EDUCATING FOR IMPACT: COMMUNITY HYGIENE AND SANITATION AWARENESS FOR HOMESTAY READINESS IN WOLOGAI TENGAH - Yulius, Kevin Gustian; Sianipar, Rosianna; Pramono, Rudy (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
This community service program was carried out in Wologai Tengah Village, Ende Regency, to enhance community awareness of hygiene and sanitation as part of early preparation for homestay-based tourism. The activity responded to the growing interest among local residents to participate in tourism by offering accommodations in modern houses located outside the sacred area of Kampung Adat Wologai. The training used lecture and discussion methods, with 20 participants. Training materials focused on personal hygiene, household sanitation, waste management, and water safety. Pre-test and post-test assessments were conducted to measure knowledge improvement. Results show that participants demonstrate significant learning gains, with individual score increases ranging from 50 to 70 percent. These results indicate a high level of community engagement and openness to tourism knowledge. The training serves as a foundation for future tourism readiness efforts and highlights the importance of integrating hygiene education into rural hospitality development. It also emphasizes the need for follow-up programs on guest handling, service quality, and sustainable tourism planning to support long-term goals. This program concludes that Wologai Tengah holds strong potential to grow into a culturally grounded rural tourism destination with the right knowledge support and planning. Keywords: community-based tourism; desa wisata; homestay; hygiene and sanitation